2005
DOI: 10.1111/j.1440-172x.2005.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutual suffering: A nurse's story of caring for the living as they are dying

Abstract: The aim of this study was to uncover the meaning of the lived experience of mutual suffering in relation to the care of a dying patient. The study took place within an acute medical ward in a district general hospital on the south coast of England as part of a reflective practice development programme. Parse's human becoming theory provided a framework for the study and Parse's research methodology was adopted. Understanding the nature of human relationships within nursing practice is central to nursing work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 15 publications
0
20
0
2
Order By: Relevance
“…As highlighted in previous studies, caring for a dying patient not only involves facing the distress of others but also evokes personal memories of losing family members (Graham et al, 2005). In addition, nurses often feel discomfort or emotional suffering because they do not know how to care for those in the process of dying (Graham et al, 2005), and these emotional stressors have been reported as value conflicts, lack of emotional support, and dealing with patient and family suffering (Ge´linas et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…As highlighted in previous studies, caring for a dying patient not only involves facing the distress of others but also evokes personal memories of losing family members (Graham et al, 2005). In addition, nurses often feel discomfort or emotional suffering because they do not know how to care for those in the process of dying (Graham et al, 2005), and these emotional stressors have been reported as value conflicts, lack of emotional support, and dealing with patient and family suffering (Ge´linas et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, nurses often feel discomfort or emotional suffering because they do not know how to care for those in the process of dying (Graham et al, 2005), and these emotional stressors have been reported as value conflicts, lack of emotional support, and dealing with patient and family suffering (Ge´linas et al, 2012). In this study, participants often experienced healing through caring for patients or dealing with their own unfinished business and through participating in the funeral and memorial services of patients.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A welcoming caring culture allows suffering human beings the right to become and be patients, as well as making it possible for them to acknowledge suffering and obtain alleviation . Graham et al . illuminated mutual suffering as a situation and process of learning about others and oneself.…”
Section: Introductionmentioning
confidence: 99%